Synthesis and pharmacological evaluation of conformationally constrained glutamic acid higher homologues. Issue 22 (15th November 2016) - Tamborini, Lucia; Cullia, Gregorio; Nielsen, Birgitte; De Micheli, Carlo; Conti, Paola; Pinto, Andrea
Graphical abstract: Abstract: Homologation of glutamic acid chain together with conformational constraint is a commonly used strategy to achieve selectivity towards different types of glutamate receptors. In the present work, starting from two potent and selective unnatural amino acids previously developed by us, we investigated the effects on the activity/selectivity profile produced by a further increase in the distance between the amino acidic moiety and the distal carboxylate group. Interestingly, the insertion of an aromatic ring as a spacer produced a low micromolar affinity NMDA ligand that might represent a lead for the development of a new class of NMDA antagonists.